ANALISIS PERAN PENGETAHUAN AKUNTANSI, PENGELOLAAN KEUANGAN, SERTA SISTEM INFORMASI AKUNTANSI DALAM MENINGKATKAN KUALITAS LAPORAN KEUANGAN - Pujiati, Eni; Nawangsari, Ajeng Tita (Jawa Dwipa, 2025)
This study was conducted to examine the role of accounting knowledge, financial management, and accounting information systems in improving the quality of financial reports. Accounting knowledge is seen as the foundation for understanding accounting standards and principles so that reports can be prepared in accordance with applicable regulations. Financial management is considered a critical factor supporting the effectiveness of planning, control, and decision-making, which is reflected in financial performance. Furthermore, accounting information systems are used to ensure that recording and reporting processes are accurate, timely, and relevant. The research method used was a literature review with a descriptive-analytical approach, allowing for systematic explanation of the relationships between variables. The results indicate that accounting knowledge, financial management, and accounting information systems contribute significantly to improving the quality of financial reports, particularly in the aspects of relevance, reliability, understandability, and comparability. It is concluded that improvements in these three aspects are necessary to achieve transparency and accountability in financial reporting.